Molecular Evidence of Emerged Pulmonary Lophomoniasis due to Lophomonas blattarum among Hospitalized Patients in Southwestern Iran: A National Registry-Based Study - Mokhtarian, Kobra; Taghipour, Simin; Nakhaei, Maryam; Taheri, Amirmasoud; Sharifpour, Ali; Fakhar, Mahdi; Ziaei Hezarjaribi, Hajar (Interdisciplinary Perspectives on Infectious Diseases, 2022)
Objectives. Lophomonas protozoan is an emerging pathogen transmitted through arthropods such as cockroaches. Lophomoniasis is still a mysterious disease with many unknown epidemiological aspects. The current study aimed to determine the prevalence of lophomoniasis among patients who were hospitalized in Hajar Hospital, Shahrekord, southwestern Iran, using a conventional PCR technique. Methods. In this retrospective study, 132 frozen bronchoalveolar lavage fluid (BALF) specimens from patients with respiratory disorders hospitalized in Hajar Hospital, Shahrekord district, southwestern Iran, were analyzed during 2020-2021. Samples are referred to the Iranian National Registry Center for Lophomoniasis (INRCL), Mazandaran Province, Northern Iran, for detecting Lophomonas spp. infection by a conventionally small subunit ribosomal RNA (SSU rRNA) PCR test. Results. A total of 132 frozen BALF specimens were examined, 36 (27.3%) tested Lophomonas spp. positive using the conventional PCR technique. Also, based on sequencing data and blast analysis, the presence of L. blattarum species was confirmed. The average age of Lophomonas spp.‐ positive patients was 67.02 ± 15.14 years. Out of the 36 positive subjects, 63.9% were male and 36.1% female. Male and Lophomonas infection had a significant correlation (p=0.001). Our findings revealed that L. blattarum infected nonsmokers more than smokers (p=0.001). The most common underlying disease was also bronchitis Conclusion. Our results showed, for the first time, that pulmonary lophomoniasis caused by L. blattarum is a common and emerging disease in the study area, southwestern Iran. Furthermore, our findings support the use of the PCR test to detect Lophomonas infection in archived frozen clinical samples.